Stability trends of Jinpingzi landslide: A numerical study - Xu, Bo; Huang, Qisong; Qian, Yuandi (Frontiers in Earth Science, 2022)
The occurrence and development of creep landslides are under gradual destruction, and it is of practical value to research their relevant stability trend based on the technique to monitor data of landslides. In this paper, Jinpingzi landslide area Ⅱ served as the background of the research, and the strength subtraction was used to analyze the relationship between the stress and strain of key points and the stability of the whole landslide. Also, the research confirmed the relationship among the creep landslides’ internal failure pattern, the safety factor, and the key point displacement; it also confirmed the change rules of displacement along with the changes in safety factor. At the same time, by combining the actual monitoring data of Jinpingzi landslide area Ⅱ, we used the research relationship to analyze its stability trend. The results show that the Jinpingzi landslide area Ⅱ is in a stable damage deformation. And it can be inferred that the sliding surface has formed in the landslide, and the results of examples are validated by exploring the geology and analyzing the field monitoring on the spot.